2010
DOI: 10.1002/jmri.22073
|View full text |Cite
|
Sign up to set email alerts
|

Apparent diffusion coefficient and fractional anisotropy in the vertebral bone marrow

Abstract: Purpose: To assess the state of cancellous tissue we analyzed the apparent diffusion coefficient (ADC) and fractional anisotropy (FA) in vertebral bone marrow.Materials and Methods: With 1.5 T magnetic resonance imaging (MRI), single-shot diffusion echo planar imaging was used with b factors of 0 and 1000 s/mm 2 , diffusionsensitizing gradient in six directions, sensitivity encoding technique, effective TE of 74 msec, and TR of 1800 msec. ADC and FA were determined in the lumbar vertebral body of 11 normal sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
3
17
4
Order By: Relevance
“…A good agreement between our FA versus T-score results and Ueda et al results obtained in vertebrae [24] was observed in the healthy group. Unlike the contradictory results obtained in vertebral cancellous bone [17,[22][23][24], a clear relationship between MD and T-score was found in the femoral neck.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…A good agreement between our FA versus T-score results and Ueda et al results obtained in vertebrae [24] was observed in the healthy group. Unlike the contradictory results obtained in vertebral cancellous bone [17,[22][23][24], a clear relationship between MD and T-score was found in the femoral neck.…”
Section: Discussionsupporting
confidence: 92%
“…Unlike the contradictory results obtained in vertebral cancellous bone [17,[22][23][24], a clear relationship between MD and T-score was found in the femoral neck. These differences between our MD results and those obtained in vertebrae, are due to a slower water dynamic investigated in this study compared to that in vertebral bone [17,[22][23][24].…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations